Control and Optimization of the Electrochemical and Mechanical Properties of the Solid Electrolyte Interphase on Silicon Electrodes in Lithium Ion Batteries. Issue 8 (5th February 2016) - Tokranov, Anton; Kumar, Ravi; Li, Chunzeng; Minne, Stephen; Xiao, Xingcheng; Sheldon, Brian W.
Abstract : The formation of the solid electrolyte interphase (SEI) on Si is examined in detail using several in situ techniques. The results show that employing different conditions during the first lithiation cycle produces SEI films with substantially different properties. Longer time at higher potentials produces softer SEI, whereas inorganic phases produced at lower potentials have higher elastic moduli. The SEI thickness stabilizes during the first cycle; however, the SEI resistance decreases during the first 20 cycles (in sharp contrast to typical surface passivation processes, where resistance is expected to increase with time). This behavior is consistent with the slow growth of inorganic constituents at lower potentials, inside of a mesoporous soft SEI that initially forms at higher potentials. This interpretation is based on the premise that these inorganic phases have a lower resistivity than that associated with electrolyte transport through the mesoporous organic phase. Based on this set of observations, the multiphase structure that evolves during initial cycling determines critical electrochemical and mechanical properties of the SEI. A basic model of these tradeoffs is proposed to provide guidelines for creating more stable interfacial films. Abstract : The formation of the solid electrolyte interphase (SEI) on Si electrodes are examined with results obtained from several in situ techniques. Varying the cycling schedule during the first lithiation cycle results in SEI films with substantially different properties, which are measured and analyzed. These observations lead to a basic multiphase SEI model that describes both mechanical and electrochemical behavior.